Telomerase-independent survival leads to a mosaic of complex subtelomere rearrangements in Chlamydomonas reinhardtii - Chaux, Frédéric; Agier, Nicolas; Garrido, Clotilde; Fischer, Gilles; Eberhard, Stephan; Xu, Zhou (Genome Research, 2023)
Telomeres and subtelomeres, the genomic regions located at chromosome extremities, are essential for genome stability in eukaryotes. In the absence of the canonical maintenance mechanism provided by telomerase, telomere shortening induces genome instability. The landscape of the ensuing genome rearrangements is not accessible by short-read sequencing. Here, we leverage Oxford Nanopore Technologies long-read sequencing to survey the extensive repertoire of genome rearrangements in telomerase mutants of the model green microalga Chlamydomonas reinhardtii. In telomerase-mutant strains grown for hundreds of generations, most chromosome extremities were capped by short telomere sequences that were either recruited de novo from other loci or maintained in a telomerase-independent manner. Other extremities did not end with telomeres but only with repeated subtelomeric sequences. The subtelomeric elements, including rDNA, were massively rearranged and involved in breakage–fusion–bridge cycles, translocations, recombinations, and chromosome circularization. These events were established progressively over time and displayed heterogeneity at the subpopulation level. New telomere-capped extremities composed of sequences originating from more internal genomic regions were associated with high DNA methylation, suggesting that de novo heterochromatin formation contributes to the restoration of chromosome end stability in C. reinhardtii. The diversity of alternative strategies present in the same organism to maintain chromosome integrity and the variety of rearrangements found in telomerase mutants are remarkable, and illustrate genome plasticity at short timescales.
10.1101/gr.278043.123